KATEGORI KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN PERSOALAN TRISEKSI SUDUT ZAMAN THALES-EUCLID - Zulhafendi, Redy Williantama (Departemen Matematika, 2024)
Angle trisection is a geometry concept that refers to the splitting of an angle into three equal parts, so that each part formed has the same angle size. This angle trisection became one of the three most interesting and unsolved mathematical problems during the last three centuries BC. Consequently, the purpose of this study is to examine the history of angle trisection in the Thales-Euclid era and measure students' ability to solve angle trisection problems. This research is a qualitative research that uses case study and literature review methods with data collection techniques through tests and interviews. The research subjects were selected by purposive sampling method from three high school students. Furthermore, the data obtained were analyzed descriptively and qualitatively with triangulation techniques. The purpose of this analysis is to ensure that the data obtained from various sources are valid. The results showed the extent of students' understanding in responding and creating how to solve this angle trisection using a ruler and a period. A detailed presentation of the categories of answers given by learners will be presented in this paper.Keywords–Angular Trisection, Thales-Euclid Era, History of Mathematics